2017
DOI: 10.1039/c7ra10699h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al content on number and location of hydroxyl acid species in zeolites: a DRIFTS quantitative protocol without the need for molar extinction coefficients

Abstract: In this work, we have systematically investigated the effect of the Al content on the number and location of bridging hydroxyls (Brønsted acid sites) and terminal hydroxyls (terminal silanol sites) in ZSM-5 zeolites with varying silica-alumina ratio (SAR ¼ SiO 2 /Al 2 O 3 ) using Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS) without molar extinction coefficients. Two base probe molecules with different kinetic diameters, pyridine (5.7Å) and collidine (7.4Å), were used. The total content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…The ν (O – H) absorption bands involving more the aluminum sites can be found, for both measured zeolites, at ca. 3590 cm −1 for Brønsted acid sites Si‐O(H)‐Al and at 3663 cm −1 for so‐called extra‐framework aluminum species (EFAL) that behave more like Lewis acids in agreement with already documented studies . Interestingly these absorption bands are broader in the spectra originally recorded for the unloaded zeolites Z16D and A, suggesting the presence of water traces in the samples able to interact via H‐bonds with Lewis and Brønsted sites .…”
Section: Resultssupporting
confidence: 87%
“…The ν (O – H) absorption bands involving more the aluminum sites can be found, for both measured zeolites, at ca. 3590 cm −1 for Brønsted acid sites Si‐O(H)‐Al and at 3663 cm −1 for so‐called extra‐framework aluminum species (EFAL) that behave more like Lewis acids in agreement with already documented studies . Interestingly these absorption bands are broader in the spectra originally recorded for the unloaded zeolites Z16D and A, suggesting the presence of water traces in the samples able to interact via H‐bonds with Lewis and Brønsted sites .…”
Section: Resultssupporting
confidence: 87%
“…The degreened sample displayed negative bands at 3584 and 3608 cm −1 , which could be assigned to the Brønsted acid sites Al-OH-Si. [34][35][36][37] The bands at 3740 cm −1 corresponded to the terminal silanols (Si-OH) vibration. 34,35,37 The band at 3652 cm −1 was less clearly assigned.…”
Section: Nh 3 Storagementioning
confidence: 99%
“…[34][35][36][37] The bands at 3740 cm −1 corresponded to the terminal silanols (Si-OH) vibration. 34,35,37 The band at 3652 cm −1 was less clearly assigned. Aufdembrink et al reported the appearance of a peak at 3650 cm −1 after the activation at 550°C of an NH 4 + -exchanged chabazite zeolite.…”
Section: Nh 3 Storagementioning
confidence: 99%
“…14,15 Recently, Bräuer et al observed that with a decrease of silicon-to-aluminum ratios in ZSM-5 crystals, the fraction of the external Brønsted sites decreases, which indicates that the distribution of aluminum over a crystal varies with the framework aluminum content. 16,17 By adopting different combinations of inorganic and organic structure-directing agents in ZSM-5 crystallization, Chawla et al found different (homogenous and heterogeneous) aluminum distributions over crystals. 18 These results suggest that the distribution of aluminum over a crystal depends on multiple factors.…”
Section: Introductionmentioning
confidence: 99%